From research to health policy: The Noguchi story in the past, present and next 25 years - Yeboah-Manu, Dorothy; Odoom, John Kofi; Osei-Wusu, Stephen; Adoma-Boakye, Afia; Osae-Amoako, Griselda; Asante-Poku, Adwoa; Akorli, Jewelna; Abuaku, Benjamin; Kusi, Kwadwo Asamoah; Ahorlu, Collins Stephen (Frontiers in Tropical Diseases, 2023)
The Noguchi Memorial Institute for Medical Research (NMIMR) is a semi-autonomous institute of the College of Health Sciences, University of Ghana, Legon. Founded in 1979, the Institute was built with a grant aid from the Government of Japan as a gift to the people of Ghana in memory of the renowned Japanese medical scientist, Dr. Hideyo Noguchi, who died from Yellow fever infection while conducting research on the disease in Ghana. The Institute has a three-pronged mandate to conduct health related research, build human capacity and provide specialized diagnostic and disease monitoring services in support of the Ghana Health Service. Over the past 40 years, the Institute has grown to be a leading biomedical research institute in the African region. It has strong and long-standing collaborations with scientists and institutions in Africa, Japan, Europe, Australia and North America on several projects on diseases of public health importance. The Institute also hosts several regional and national centres such as Regional Influenza laboratory. The Institute’s research activities are relevant to the control and prevention of infectious diseases in Ghana, particularly, HIV/AIDS, Tuberculosis, Buruli ulcer, Polio, Malaria and emerging infectious diseases. The Institute also plays a technical/advisory role to government through collaborations with disease control programmes and has since inception provided the country with needed critical evidence in support of health policy as well as laboratory diagnostic services among others. Going forward, the Institute seeks to expand and consolidate its activities in areas of antimicrobial resistance (AMR), clinical trials, genomic surveillance and academic programs and in the next 25 years, NMIMR hopes to approach every research area using the one health approach.